Sieve tubes diameter and the rubber production in rubber tree clones - Assini A; Goncalves P de S; Gondim-Tomaz R M A (Bragantia, 1998)
Sieve tubes diameters of 15 rubber trees clones, eleven years old [Hevea brasiliensis (Willd. ex. Adr. de Juss.) Muell Arg.] accounting for plant materials with high (IAN 873, IAC 41, RRIM 600, PR 107, IAN 717, IAC 57 and IAC 15) and low (IAC 53, IAC 39, IAC 59, IAC 51, IAC 16, IAC 22, IAC 19 and IAC 9) rubber productions were determined. Results have shown significant correlation (R2=0.825)between sieve tubes diameter and rubber production (y=0.1961x2 - 14.77x + 281.7)
Keywords: Hevea brasiliensis; Rubber production; Sive tubes